2007
DOI: 10.1007/s10681-007-9420-8
|View full text |Cite
|
Sign up to set email alerts
|

Genotype × environment interaction and yield stability in a cowpea-based cropping system

Abstract: Twenty-four cowpea genotypes were evaluated under sole cropping or additive series intercropping with sorghum from 2004 to 2005 at four sites representative of the Guinea and Sudan savannah ecologies in Ghana. The aim was to determine whether cowpea breeding programs that emphasize selection under sole-crop conditions have the potential to produce cultivars that are effective under additive series intercropping. Genotype · cropping systems interaction was significant for days to 50% flowering but not for grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…These results indicated that cowpea genotypes responded differently to different environmental conditions, suggestion the importance of assessment of genotypes under different environments in order to identify the best genetic make up for particular environment. These results appeared to be in harmony with those obtained by Nwofia et al (2007), Padi (2007), Peksen (2007, De Rocha et al (2007 a,b), Sarutayophat et al (2007) and Taiwo (2007).…”
Section: Total Dry Seed Yield (Ton/fed)supporting
confidence: 90%
“…These results indicated that cowpea genotypes responded differently to different environmental conditions, suggestion the importance of assessment of genotypes under different environments in order to identify the best genetic make up for particular environment. These results appeared to be in harmony with those obtained by Nwofia et al (2007), Padi (2007), Peksen (2007, De Rocha et al (2007 a,b), Sarutayophat et al (2007) and Taiwo (2007).…”
Section: Total Dry Seed Yield (Ton/fed)supporting
confidence: 90%
“…Songotra produce the highest pod per plants, followed by T 2 T 4 and Padi-tuya recorded the least pods per plant. This result is in conformity with [18][19][20] who reported that the number of pods per plant is the most important component in determining yield in several legume crops.…”
Section: Yield and Yield Componentssupporting
confidence: 92%
“…A caution with the early generation section approach is, however, that strong genotype  environment interaction for grain yield has been documented in cowpea in the northern savannah belt of West Africa (Padi, 2007b), and the probability of obtaining families with broad adaptation to the target production belt is higher when a high proportion of elite families are tested in advanced multilocation evaluations. Although this has been achieved mainly based on the single-seed descent breeding approach, retrospective selection in the F 3 suggests that a pedigree breeding approach would have been effective as well, with less transaction costs related to the number of families that are screened in replicated tests.…”
Section: Discussionmentioning
confidence: 99%
“…Although this has been achieved mainly based on the single-seed descent breeding approach, retrospective selection in the F 3 suggests that a pedigree breeding approach would have been effective as well, with less transaction costs related to the number of families that are screened in replicated tests. A caution with the early generation section approach is, however, that strong genotype  environment interaction for grain yield has been documented in cowpea in the northern savannah belt of West Africa (Padi, 2007b), and the probability of obtaining families with broad adaptation to the target production belt is higher when a high proportion of elite families are tested in advanced multilocation evaluations. A low selection pressure is, therefore, necessary in early generation selection for these production regions.…”
Section: Discussionmentioning
confidence: 99%